Hybrid Natural and Forced Active Balancing Control of Battery Packs State of Charge Based on Partnership for a New Generation of Vehicles. (4th December 2018) - Wei, Yewen; Dai, Shuailong; Wang, Jiayu; Shan, Zhifei; Min, Jie
Abstract : Battery packs are widely used in electric vehicles, and their state-of-charge is one of the essential issues that affect the performances, whilst the balance between parallel and series cell of the battery pack always has an obvious effect. To enhance the working performance of the lithium-based power battery pack, a hybrid natural and forced active balancing control (HNFABC) strategy is proposed and adopted to the balancing circuit that is proposed in this work. These converters, which are advantageous in natural balancing and forced equalization, accelerate the balance speed of natural equilibrium in the final stage and protect the battery from being repeatedly charged and discharged. Simulation and experimental results show that HNFABC is not only simpler than other traditional balance control strategies but also faster in the equalization process. The idea of combining natural equilibrium and forced equilibrium can be inspired to be used in some related industries.